Análisis, diseño e implementación de un módulo de comercio electrónico y gestión de empresas integrado al proyecto GeoBuy del Centro de Investigación, Desarrollo e Innovación Tecnológica. - Morocho Cuenca, Ángel Rigoberto (2013)
The GEOBUY project (acronym for "BUY" shopping and "GEO" geolocation), is developed in order to mitigate needs of virtual marketing to ensure the reliability of shopping online, with the use of maps and can thus both users and businesses get to more easily meet the needs of a world potential.